The Fact of How Leaders Influence on Employee Creativity in Indonesia - B. Medina Nilasari; Salut Muhidin; Ditho Dwi Prasetyo (Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: Digitization in the Indonesian National Shipping Company requires employee creativity so it is necessary to know the extent of the role of transformational leadership. The purpose of this study is to analyze the effect of transformational leadership on employee creativity at the Indonesian National Shipping Company. Background Problems: The demand for employee creativity is very high at this company engaged in ship transportation services because the use of technology and digitalization in the workplace environment is increasing to minimize physical contact when carrying out task activities. Therefore, the role of transformational leadership is needed in increasing employee creativity to generate innovative ideas and work behavior. Novelty: Compared to previous studies, this study also examining perceived organizational support as a mediating variable of the effect of transformational leadership on employee creativity. Research Methods: The data used in this study are primary data. 200 respondents were obtained from Indonesian National Shipping Company who became the sample. Analysis of the data used to test the hypothesis is Structural Equation Modeling (SEM). Finding/Results: Transformational leadership affects employee creativity and the effect of transformational leadership on employee creativity can be mediated by perceived organizational support. In addition, the higher the employee's perception of perceived organizational support, the stronger the effect of transformational leadership on employee creativity. Conclusion: Leaders who motivate, inspire, have quirky ideas, are willing to listen, and leaders who encourage employees to develop can increase employee creativity. The more leaders care about employees' opinions, leaders care about employee welfare, leaders are consistent with procedural justice, and fairness according to employee performance, the perceived organizational support will improve which will then strengthen the effect of transformational leadership on employee creativity.